EVALUASI JARINGAN TEGANGAN MENENGAH SISTEM KELISTRIKAN KAMPUS UNIVERSITAS TADULAKO MENGGUNAKAN ETAP 7.5.0 - Santiyasa, I Nyoman; Sarjan, Muhammad; Rahman, Yuli Asmi (FORISTEK : Forum Teknik Elektro dan Teknologi Informasi, 2014)
Electricity is a secondary energy form that is generated, transmitted and distributed for all kinds of purposes. Tadulako University Campus an electricity consumer with considerable power and continue their development rapidly. Because of the construction, the electrical load is also increasing, the medium-voltage network as one of the components of the power system needs to be evaluated in order to serve the load capacity continuously. Electrical power is supplied from distribution transformers to user have voltage loss and power losses. Because the distribution network has resistance, inductance, and capacitance. The energy lost already appeared from the generation system. This study was conducted by analyzing model of the single line diagram with input medium voltage-network Tadulako University campus data in ETAP 7.5.0 application. From the analysis, there were losses in the medium voltage network Tadulako University Campus at 1.358% with 0.39% voltage drop at the existing load. Keywords : Electricity, Losses, Drop Voltage, Medium Voltage Networks, ETAP